Optimization of T-shape slotted quartz tube with exit holes-atom trap-flame atomic absorption spectrophotometry system for the accurate and sensitive determination of tellurium in tap water - Sahin, Ipek; Durak, Busra Yilmaz; Sagsoz, Oguzhan; Buyukpinar, Cagdas; Bakirdere, Sezgin (SPRINGER, 2020)
Tellurium has been widely used in industrial processes and daily life products, and can cause serious health problems upon exposure. Therefore, determination of tellurium in real-life samples is very crucial. In this study, an accurate, environmentally friendly, and inexpensive analytical method was developed to determine trace levels of tellurium in water samples. To lower the detection limits, system parameters including flame type, acetylene flow rate, slotted quartz tube (T-SQT) height, and trapping period were optimized. Under the optimum conditions, the limit of detection (LOD) and quantification (LOQ) were calculated as 14.1 ng/mL and 47.1 ng/mL, respectively. For recovery studies, the optimized T-SQT-AT-FAAS method was applied to tap water samples to determine trace levels of tellurium and recovery results were found between 91.1 and 111.3%. Relative standard deviation value (%RSD) of the developed method was found to be less than 5.0% even for the lowest concentration in calibration plot, specifying good accuracy and high applicability of the method for water samples. Graphical abstract .
Keywords: Tellurium; Atom trap; Slotted quartz tube; Hydrogen; Flame atomic absorption spectrophotometry; Tap water; SPECTROMETRY; Environmental Sciences & Ecology